(untitled) - Heaton, Charlie; 1994-; Braga, Alice; Hunt, Blu; Zaga, Henry; Beach, Adam; 1972-; 1996-; 1995-; 1993-; Taylor-Joy, Anya; Boone, Josh; et al. ([Los Angeles, CA], 2020)
In this terrifying, action-fueled film based on the Marvel comic series, five young people who demonstrate special powers are brought to a secret institution to undergo treatments they are told will cure them of the dangers of their powers. Invited by Dr. Cecilia Reyes to share their stories about when their powers first manifested, the five 1patients2 come to understand that they are in a class of people called mutants, who have historically been marginalized and feared.
Keywords: Teenagers; Drama; Drama; New Mutants (Fictitious characters); Superhero films; Horror films; Science fiction films; Action and adventure films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Drama; Fiction films; Feature films; Fiction films; Horror films; Drama; Superhero films; Feature films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities